NEW DEVELOPMENT OF POTENTIAL THEORY FOR THE CLUSTER PHOTODISINTEGRATION OF LIGHT NUCLEI - Burkova, N.A.; Zhaksybekova, K.A.; Zhusupov, M.A. (Recent Contributions to Physics, 2008)
The new development of created by authors the potential photodisintegration theory is treated. Under the detailed discussion are the reactions and , which have being calculated early by other theorists show good qualitative reproduction of the experimental data, but to our opinion they are not satisfy and even contradict to the physics of the photoprocesses.